Host‐range studies, genetic diversity and evolutionary relationships of ACLSV isolates from ornamental, wild and cultivated Rosaceous species. (4th April 2013) - Katsiani, A.T.; Maliogka, V. I.; Candresse, T.; Katis, N. I.
<x xml:space="preserve">Abstract</x> A large‐scale survey was carried out to study the host range and genetic diversity of Apple chlorotic leaf spot virus (ACLSV) in various Rosaceae species, with a special emphasis on ornamentals and wild shrubs. Samples were tested by DAS‐ELISA using two different antisera, and RT‐PCR amplification of part of the CP gene. There was generally a poor correlation between the results obtained with the two sets of serological reagents and between serological and molecular detection assays. Using a nested RT‐PCR assay developed here, ACLSV was found to be widespread among cultivated, ornamental and wild species of the Rosaceae. The virus was detected for the first time in plum, wild cherry, Crataegus monogyna, Prunus spinosa and Prunus cerasifera in Greece. Sequences of a part of the CP encoding gene and the 3′ untranslated region from ACLSV isolates originating from various wild species and ornamentals were compared to those of isolates from cultivated hosts, showing similar divergence levels. Further phylogenetic analysis using the sequenced region indicated that the isolates from wild or ornamental hosts were not more closely related to each other than to isolates from cultivated hosts. The possible role of different factors in the spread of ACLSV on cultivated, ornamental and wild species is discussed.